6-Butyl-5-(4-methoxyphenoxy)-3-phenyl-3H-1,2,3-triazolo[4,5-d]pyrimidin-7(6H)-one - Hong-Mei Wang; Ping Chen; Shou-Heng Deng; Xiao-Hua Zeng; Zuan Ma (Acta Crystallographica Section E, 2009)
The asymmetric unit of the title compound, C21H21N5O3, consists of two geometrically similar molecules. The fused rings of the triazolo[4,5-d]pyrimidine system are nearly coplanar, making dihedral angels of 1.48 (18) and 1.34 (16)°, and the phenyl rings are twisted by 12.3 (1) and 8.7 (1)° with respect to the triazolopyrimidine plane. The ethyl groups of the n-butyl side chains are disordered over two sites in each of the independent molecules, the ratios of occupancies being 0.60:0.40 and 0.61:0.39.